Asthmatic children from lower‐income families are less likely to own an individualised asthma action plan. (26th June 2019) - Harrison, Philippa; Duggan, William; Preddy, John; Moline, Adrienne
Abstract : Aim: This study aimed to explore the relationship between indicators of socio‐economic status (SES) and prescription of a paediatric individualised asthma action plan (IAAP), as well as compliance with that plan. Methods: Between May and September 2017, parents/carers of children aged 2–16 years who presented with acute respiratory symptoms and a prior diagnosis of asthma to the emergency department at one regional and one metropolitan hospital in NSW, Australia, were invited to participate in a questionnaire‐based study. Results: A total of 175 eligible participants were identified, of which 113 completed the questionnaire. Eighty‐seven children had been prescribed an IAAP (77%). Forty‐nine parents/carers reported non‐compliance with that plan (56.3%). Children from low‐ to middle‐income families were significantly less likely to have a plan ( P = 0.001). Being an only child was associated with greater IAAP compliance ( P = 0.007) and better asthma control ( P = 0.035). No significant relationship between other indicators of SES and rates of plan ownership or compliance was demonstrated. Conclusion: Although relatively high in our study sample, IAAP ownership rates remain well below published guidelines. Given the income‐based disparity in plan ownership, physicians must routinely prescribe plans to all asthmatics. Strategies to ensure IAAP ownership and promote their use, especially in the public health sector, would be valuable. Repeating a similar study with a larger sample size will allow more robust conclusions to be drawn regarding the impact of parental SES on compliance.